2020
DOI: 10.1111/1467-6427.12308
|View full text |Cite
|
Sign up to set email alerts
|

Digital systemic practices in Europe: a survey before the Covid‐19 pandemic

Abstract: Knowledge regarding digital practices in the field of systemic therapy is poor. A few surveys have been conducted in non‐European countries investigating the provision of digitally based therapy, counselling, training, and supervision by systemic family and couple therapists (SCFTs). Thus, a survey aiming to investigate the use of information and communication technology (ICT) among European SCFTs was launched in 2017. A sample of 220 SCFTs was included in the survey. The majority were residents in Greece, Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(82 reference statements)
2
8
0
1
Order By: Relevance
“…Borcsa and Pomini, 2017; Wrape and McGinn, 2018), but a European survey of 252 systemic couple and family therapists, which included 6 respondents from the UK, revealed that, although 81% had used information and communication technology (ICT) for clinical communication (e.g. email), only 4% had worked with families online (Borcsa et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Borcsa and Pomini, 2017; Wrape and McGinn, 2018), but a European survey of 252 systemic couple and family therapists, which included 6 respondents from the UK, revealed that, although 81% had used information and communication technology (ICT) for clinical communication (e.g. email), only 4% had worked with families online (Borcsa et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the transforming practice, in which we combine the use of eHealth with the involvement of a network and thus involving more persons, it might be even more complicated to ensure a therapeutic alliance. The experiences in the field of digital systemic practices (e.g., digital family therapy) [ 61 ] may give new insights into how to deal with this complexity, even though it is a relatively new study field [ 62 ]. For example, research shows that family therapists need to develop complex communication skills to engage with multiple clients through eHealth.…”
Section: Discussionmentioning
confidence: 99%
“…Κύρια άλλα πλεονεκτήματα των ψηφιακών πρακτικών στην παροχή υπηρεσιών ψυχικής υγείας είναι η εξοικονόμηση πόρων και χρόνου, η ευελιξία, η δυνατότητα συνεργασίας με άτομα που ταξιδεύουν συχνά ή μεταφέρονται σε άλλον τόπο, η δυνατότητα άμεσης παροχής βοήθειας καθώς και η διευκόλυνση της αρχικής κινητοποίησης με στόχο την προετοιμασία συνάντησης πρόσωπο με πρόσωπο (face-to-face) (Borcsa, Pomini, & Saint Mont, 2021).…”
Section: η θεραπευτική σχέση στις ψηφιακές πρακτικέςunclassified